Dissimilar metal joining of stainless steel and titanium using copper as transition metal - Pardal, Goncalo; Ganguly, Supriyo; Williams, Stewart W.; Vaja, Jay (Springer, 2016)
Joining of stainless steel and titanium dissimilar metal combination has a specific interest in the nuclear industry. Due to the metallurgical incompatibility, it has been very difficult to produce reliable joints between these metals due to the formation of FeTi and Fe2Ti types of intermetallic compounds. The metallurgical incompatibility between both materials is enhanced by the time–temperature profile of the welding process used. Brittle intermetallics (IMCs) are formed during Fe–Ti welding (FeTi and Fe2Ti). The present study uses the low thermal heat input process cold metal transfer (CMT), when compared with conventional GMAW, to deposit a copper (Cu) bead between Ti and stainless steel. Cu is compatible with Fe, and it has a lower melting point than the two base materials. The welds were produced between AMS 4911L (Ti-6Al-4V) and AISI 316L stainless steel using a CuSi-3 welding wire. The joints produced revealed two IM layers located near the parent metals/weld interfaces. The hardness of these layers is higher than the remainder of the weld bead. Tensile tests were carried out with a maximum strength of 200 MPa, but the interfacial failure could not be avoided. Ti atomic migration was observed during experimental trials; however, the IMC formed are less brittle than FeTi, inducing higher mechanical properties.
Keywords: Titanium; Stainless steel; Intermetallic; Dissimilar welding